Career paths in online labor markets: Same, same but different? - Mareike Seifried; Roman Jurowetzki; Tobias Kretschmer (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
The emergence of online labor markets calls the validity of traditional career models into question. Given the volatility and digital nature of this environment, short-term employment relationships and heterogeneity of workers, employers and tasks in these markets, it is unclear how careers might unfold - whether they are largely random and accidental or whether there are distinct trajectories and patterns in online careers. We document dominant career paths and develop a taxonomy of novel career patterns in OLMs. This addresses recent calls for research to update and refine our theories and understanding of careers (Rahman et al., 2016). We adopt a quantitative-inductive approach to describe workers' careers in terms of their task and skill specialization. This helps us understand the different types of careers on a continuum between more stable and random, unsystematic careers. Our results provide an innovative way of thinking about career development in OLMs and open up several fruitful areas of future research.
Keywords: J24; J44; O30; 330; online labor markets; platforms; gig economy; career theory; freelancing; labor specialization; human capital